Atomic-layer-deposition alumina induced carbon on porous NixCo1−xO nanonets for enhanced pseudocapacitive and Li-ion storage performance - Guan, Cao (2016)
A unique composite nanonet of metal oxide@carbon interconnected sheets is obtained by atomic layer deposition (ALD)-assisted fabrication. In this nanonet structure, mesoporous metal oxide nanosheets are covered by a layer of amorphous carbon nanoflakes. Specifically, quasi-vertical aligned and mesoporous NixCo1−xO nanosheets are first fabricated directly on nickel foam substrates by a hydrothermal method. Then, an ALD-enabled carbon coating method is applied for the growth of carbon nanoflakes on the surface of the nanosheets. The thus formed 3D hierarchical structure of NixCo1−xO@carbon composite flakes have a higher surface area, better electrical conductivity and structure stability than the bare NixCo1−xO. The application of such composite nanomaterials is demonstrated as electrodes for a supercapacitor and a lithium-ion battery. In both tests, the composite electrode shows enhancement in capacity and cycling stability. This effective composite nanostructure design of metal oxides@carbon flakes could provide a promising method to construct high-performance materials for energy and environment applications.